Protecting intellectual property rights in Syria and keeping pace with legislative and technical developments (Blockchain as a model) (Damascus University Journal of arts and humanities sciences, 2023)
The field of intellectual property rights is one of the areas that have witnessed concerted efforts for many years between the efforts of all countries of the world because invention and creativity cannot flourish and result in a marketing product if a strong legal system is not built to protect it, and for the importance of this, the study dealt with some basic concepts in intellectual property rights and works Digital, and focused mainly on laws and legislation related to the protection of intellectual property rights in the digital environment, including the DMCA law, and the technical procedures for protecting intellectual property in the digital environment were also highlighted by focusing on blockchain technology, which provided distinct technical protection for creativity, literature, and others. Going through the presentation of intellectual property rights laws in Syria and ending with determining the extent to which they keep pace with legislative and technical developments, especially the Blockchain, based on the case study approach. Blockchain on the other hand
Keywords: Intellectual property; Laws and legislation; - Blockchain; - Deposit engine - Syria.